Maverick management : strategies for success - Giacco, Alexander F. (Cultural studies of Delaware and the Eastern Shore., 2003)
"Maverick Management: Strategies for Success is the memoir of Al Giacco, the former Chairman and CEO of Hercules. Giacco is a maverick who succeeded because he was willing to take risks using innovative approaches in identifying what needed to be done and never quitting until it was done. A problem-solving chemical engineer who used innovation to make sure things got done in the most effective way, he ignited the creative forces at Hercules to launch it to success in the aerospace industry. It is also the story of a number of innovations in advanced management technology, including the development of a corporate computer network at a time when many business leaders questioned the use of computers as a management tool."--BOOK JACKET.